Intervention in the Interest of Deprived Elderly People - Vajda, Norbert (Journal of Educational, Health and Community Psychology, 2015)
AbstractBeside we have to have adequate answers for our material needs we must have active relationships withÂ our social environment as well. People living in segregated circumstances have limited access to the restÂ of the society, but elderly people of these fields can be mentally separated from their own communitiesÂ too, according to recent research results in Hungary.In every society of the world, external intervention for inhabitants must be based on relevant information.Â This has got two main resources: the first one is the theoretical framework of group processes; the secondÂ is the practical knowledge of the special territory where the programs can be implemented.This paper has got three main chapters. From the âIntroductionâ the Reader will understand a specialÂ element of social inequalities, when we are going to concentrate on the determinant role of residentialÂ segregation. In the second chapter we will deal with the disintegration process and the decayingsolidarity level of small communities, which has a major impact on elderly care. After we introduced theÂ details of this question, we will provide a good example for intervention in the interest of people living inÂ smaller settlements with dementia. In the âConclusionâ we will summarize the main points, withonwards thoughts about further development.Keyword: Elderly, deprived groups, social intervention, and dementia